2002
DOI: 10.1002/j.2050-0416.2002.tb00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification of Acetic Acid Esterase from Malted Barley

Abstract: Partial purifications (84, 114 and 390 fold) of a soluble acetic acid esterase from barley malt that degrades diacetin have been achieved. Enzyme recoveries were 20%, 20% and 25% in three consecutive runs. Initial problems of high viscosity and colour in the extract were overcome with the use of batch-elution anion exchange chromatography. This was followed by gradient elution anion exchange chromatography and gel filtration chromatography, which gave the greatest purification, but which gave erratic estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…By SDS-PAGE a single subunit protein band with an estimated M r of 19.7 kDa was observed (Figure 3a). The apparent molecular mass, determined under denaturing conditions, is comparable to the ones reported from the acetyl xylan esterases isolated from Pencillium purpurogenum (32), Bacillus pumilus (36) and acetic acid esterase from Barley malt (16). The estimated M r of acetic acid esterase under nondenaturing conditions using Sephacryl S-200 was found to be 79.4 kDa (Figure 3b), indicating it to be a homotetramer similar to the one reported from acetyl xylan esterase of Bacillus pumilus (36).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…By SDS-PAGE a single subunit protein band with an estimated M r of 19.7 kDa was observed (Figure 3a). The apparent molecular mass, determined under denaturing conditions, is comparable to the ones reported from the acetyl xylan esterases isolated from Pencillium purpurogenum (32), Bacillus pumilus (36) and acetic acid esterase from Barley malt (16). The estimated M r of acetic acid esterase under nondenaturing conditions using Sephacryl S-200 was found to be 79.4 kDa (Figure 3b), indicating it to be a homotetramer similar to the one reported from acetyl xylan esterase of Bacillus pumilus (36).…”
Section: Resultssupporting
confidence: 73%
“…were determined using 4-methylumbelliferyl acetate at 0.45 and 0.52 mM, respectively (38). A K m value of 25 mM for barley malt acetic acid esterase was reported using diacetin as the substrate (16). No information is available with respect to the detailed kinetics and substrate specificity of cereal/millet acetic acid esterases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation obtained displayed esterase activity with pNPA and α-naphthyl acetate but also with acetylated xylan, confirming the proposal of Ward and Bamforth (2002) that the slow migrating esterases are AXE. Humberstone and Briggs (2002a) previously reported an acetic acid esterase from malt. The rate of thermal inactivation of esterase activity in this preparation was similar (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gel filtration was used as the third step in the purification. Previous gel filtration experiments used to purify acetyl esterase from barley malt 19 had shown that the best running buffer for the column contained both glucose (0.5M) and NaCl (2.5%). These additions had reduced interactions of the extract proteins with the column matrix.…”
Section: Urwhlqmentioning
confidence: 99%